2021
DOI: 10.1039/d0cp05952h
|View full text |Cite
|
Sign up to set email alerts
|

Shape changes and budding of giant vesicles induced by an internal chemical trigger: an interplay between osmosis and pH change

Abstract: Shape transformation and self-division of phospholipid/fatty acid giant hybrid vesicles can be induced by an internal chemical stimulus (pH change) when coupled with an osmotic shock. In particular, an autocatalytic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 58 publications
0
33
0
Order By: Relevance
“…A shift towards basic conditions inside the vesicles lumen causes the deprotonation of HOA to form oleate molecules readily dissolved in the aqueous medium. In a previous work [ 31 ], we demonstrated that the addition of urea in the outer solution generates an hypertonic condition, which, in turn, drives a deflation of the vesicles due to the osmotic shock. Thus, the addition of urea triggers a synergistic dynamics between the reduction of the vesicles volume ( changes from 1 to ∼0.7 at mM and ) and the increase of the area difference between the lipid leaflets in the bilayer, caused by the dissolution of oleate molecules in the aqueous lumen ( changes from 1 to ∼1.7 at mM and ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A shift towards basic conditions inside the vesicles lumen causes the deprotonation of HOA to form oleate molecules readily dissolved in the aqueous medium. In a previous work [ 31 ], we demonstrated that the addition of urea in the outer solution generates an hypertonic condition, which, in turn, drives a deflation of the vesicles due to the osmotic shock. Thus, the addition of urea triggers a synergistic dynamics between the reduction of the vesicles volume ( changes from 1 to ∼0.7 at mM and ) and the increase of the area difference between the lipid leaflets in the bilayer, caused by the dissolution of oleate molecules in the aqueous lumen ( changes from 1 to ∼1.7 at mM and ).…”
Section: Resultsmentioning
confidence: 99%
“…For a few years our group has been studying a simple cell model having a diameter larger than 5 m (GUV) and based on a mixed phospholipid/fatty acid membrane encapsulating a pH clock reaction. We demonstrated that a simple pH change inside the vesicles lumen, coupled with an osmotic stress, is enough to induce shape transformations of the vesicles eventually leading to the fission of a mother GUV into two daughter GUVs [ 30 , 31 ]. Interestingly, our operative conditions are compatible with the slightly acidic pH suggested for the early Archean age oceans [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations